Krytyka metodologiczna jako praktyka tworzenia wiedzy (dziedziny problemowe – próba rekonstrukcji) (Krytyka metodologiczna w praktyce tworzenia wiedzy, 2019)
The aim of the study is to reconstruct various ways of understanding methodological critique as a practice of knowledge creation and to indicate, revealed in connection with the reconstruction, the possibility of identifying cognitive obstacles that arise in this practice. Methodological critique is understood as a kind of practice – the field of thinking and acting – related to the experience and rationalization of the gap between the obviousness (faith) and the uncertainty of beliefs about reality. Various ways of formulating critique, related to the treatment of critique as the value underlying the ideal of rationality of science as well as a communication strategy, are discussed. Different ways of understanding critique legitimated under the distinguished concepts of methodology (as the theory of the application of laws of logic in various areas of research and a specialized discipline concerning the place of science in the system of human knowledge), are also discussed. On this basis, the possibilities of practicing a "critical methodology", designed as a study of methods for criticizing scientific practice in the changing cultural framework, are considered. In connection with the identified processes of their change (institutionalization of science, corporatization and networking of research), patterns of practicing critique justified by methodological premises (dogmatism, conventionalism and tactical discretion) were reconstructed and confronted with the cultural patterns of critique formed on their basis (inhibition, tolerantism and presentism).